Review of systematic reviews on mandibular advancement oral appliance for obstructive sleep apnea: The importance of long-term follow-up - Kazumichi Sato; Tsuneya Nakajima (Elsevier, 2020)
Summary: The purpose of this review was to present the currently available information on oral appliance (OA) therapy for dentists, especially clinic-based dentists, to aid them in performing this treatment for the management of symptoms of obstructive sleep apnea (OSA). The clinical research evidence comprised of systematic reviews concerned with the mandibular advancement oral appliance (OAm). Continuous positive airway pressure (CPAP) is superior to OA therapy in improving OSA symptoms. It is necessary to survey the adherence of patients who stopped CPAP therapy to OAm therapy. There is little evidence supporting the theory that OAm therapy prevents cardiovascular disease or improves prognosis. There is still room to investigate the types of OAm. OAm therapy has clear dental and skeletal side effects with long-term use, and these are important for dentists. However, a certain percentage of patients discontinue consultations. Regarding consultation rate for follow-up and repair/adjustments of OAm, there are advantages for the clinic-based dentists treating OSA with OAm. We believe that enhancing under-graduate and post-graduate education on sleep medicine, and establishing a specialist system could be the strategies for enabling the dentists to handle OAm therapy in dental clinics.